Measurement of the Indirect Band Gap of Diamond with EELS in STEM. Issue 22 (30th July 2018) - Korneychuk, Svetlana; Guzzinati, Giulio; Verbeeck, Jo
Abstract : In this work, a simple method to measure the indirect band gap of diamond with electron energy loss spectroscopy (EELS) in transmission electron microscopy (TEM) is showed. The authors discuss the momentum space resolution achievable with EELS and the possibility of deliberately selecting specific transitions of interest. Based on a simple 2 parabolic band model of the band structure, the authors extend our predictions from the direct band gap case discussed in previous work, to the case of an indirect band gap. Finally, the authors point out the emerging possibility to partly reconstruct the band structure with EELS exploiting our simplified model of inelastic scattering and support it with experiments on diamond. Abstract : A simple method to measure the indirect band gap of diamond with electron energy loss spectroscopy (EELS) in transmission electron microscope (TEM) is demonstrated. The importance of the momentum resolution achievable with EELS is shown both experimentaly and on a simple 2 parabolic band model. The possibility to deliberately select specific interband transitions is discussed as well.